2020
DOI: 10.1016/j.bjps.2020.01.031
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the wound healing process after the application of three dermal substitutes with or without basic fibroblast growth factor impregnation in diabetic mice

Abstract: are approved artificial dermis products in Japan. Previously, we proved that Pelnac Gplus R was able to sustain basic fibroblast growth factor (bFGF) and accelerated wound healing by releasing impregnated bFGF. In this study, we impregnated Pelnac Gplus R , Integra R , and Terudermis R with bFGF and compared the binding activity and wound-healing process. We applied bFGF to each material and compared the bFGF concentrations in the surrounding area after 24-h incubation. For the in vivo study, dermal substitute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 24 publications
0
19
0
2
Order By: Relevance
“…Since, a one-step skin grafting and a split-thickness skin graft approach to cover the wound at the same time is desirable, numerous bi-layer skin substitutes have been developed for the management of full-thickness skin defects, such as Alloderm ® [ 19 , 20 ], Integra ® [ 21 ], Pelnac ® [ 22 ], and Matriderm ® [ 23 , 24 ]. These commercial matrices are all produced with collagen of bovine, porcine, and equine origin.…”
Section: Introductionmentioning
confidence: 99%
“…Since, a one-step skin grafting and a split-thickness skin graft approach to cover the wound at the same time is desirable, numerous bi-layer skin substitutes have been developed for the management of full-thickness skin defects, such as Alloderm ® [ 19 , 20 ], Integra ® [ 21 ], Pelnac ® [ 22 ], and Matriderm ® [ 23 , 24 ]. These commercial matrices are all produced with collagen of bovine, porcine, and equine origin.…”
Section: Introductionmentioning
confidence: 99%
“… 9 Moreover, an in vivo study showed that Pelnac Gplus impregnated with bFGF accelerates capillary formation, granulation tissue formation, and epithelialization. 10 We hypothesize that combination with negative pressure wound therapy could obtain even faster tissue granulation.…”
Section: Discussionmentioning
confidence: 99%
“…Integra® Dermal Regeneration Template (Integra Life Sciences Corporation, Plainsboro, New Jersey, US) was the first dermal skin substitute product approved by the US Food and Drug Administration (FDA). It consists of a porous matrix of cross-linked bovine tendon collagen type I, shark chondroitin-6-sulfate GAG and covered by a semi-permeable silicone membrane [47,[49][50][51][52][53]. Chondroitin-6-sulfate GAG has been shown to have antiinflammatory effect on macrophages; however, when the effects of Integra® on macrophage phenotype was analysed, a temporal down-regulation of 'M2a' macrophages (ECM deposition macrophages) was observed [54,55].…”
Section: Skin Substitutesmentioning
confidence: 99%